Un proyecto alternativo para el desarrollo urbano regional de Valparaíso - Santa María, Ignacio (Revista EURE - Revista de Estudios Urbano Regionales, 1988)
As a conceptual framework, the present study proposes the incorporation of six factors pertaining to the Territorial Conditioning field of the current criteria applied in Chile for the socio-economic evaluation of public investment, particularly those projects oriented to achieve the urban-regional development of the port-city of Valparaíso in its future geopolitical role as the Chilean and Latin American Southern Cone faí§ade to the Pacific basin. The paper presents some of the measures put forward for the revaluation of the urban vocation of port-cities such as London and Nantes Saint Nazaire as locally adaptable models. Proposing the creation of an Industrial Port and three alternative locations within the Valparaíso region, considering the proposal as the Í€œurban implantÍ€ that would best suit the objectives of urban-regional development.